Performance measures for endoscopic retrograde cholangiopancreatography and endoscopic ultrasound: A European Society of Gastrointestinal Endoscopy (ESGE) Quality Improvement Initiative. Issue 10 (December 2018) - Domagk, Dirk; Oppong, Kofi W; Aabakken, Lars; Czakó, Laszlo; Gyökeres, Tibor; Manes, Gianpiero; Meier, Peter; Poley, Jan-Werner; Ponchon, Thierry; Tringali, Andrea; Bellisario, Cristina; Minozzi, Silvia; et al.
The European Society of Gastrointestinal Endoscopy (ESGE) and United European Gastroenterology present a short list of key performance measures for endoscopic ultrasound (EUS) and endoscopic retrograde cholangiopancreatography (ERCP). We recommend that endoscopy services across Europe adopt the following seven key and one minor performance measures for EUS and ERCP, for measurement and evaluation in daily practice at centre and endoscopist level:1 Adequate antibiotic prophylaxis before ERCP (key performance measure, at least 90%);2 antibiotic prophylaxis before EUS-guided puncture of cystic lesions (key performance measure, at least 95%);3 bile duct cannulation rate (key performance measure, at least 90%);4 tissue sampling during EUS (key performance measure, at least 85%);5 appropriate stent placement in patients with biliary obstruction below the hilum (key performance measure, at least 95%);6 bile duct stone extraction (key performance measure, at least 90%);7 post-ERCP pancreatitis (key performance measure, less than 10%); and8 adequate documentation of EUS landmarks (minor performance measure, at least 90%). This present list of quality performance measures for ERCP and EUS recommended by the ESGE should not be considered to be exhaustive; it might be extended in future to address further clinical and scientific issues.